MULTIVARIATE ANALYSIS OF 31 PHENOTYPIC TRAITS AMONG MAJOR PARENTAL LINES OF SUGARCANE BREEDING PROGRAMS IN CHINA - J. Wu1; Q. Wang1; Y. B. Pan; J. Xie; F. Zhou; H. Xu; Y. Qiu; C. Zhang; Z. Liu (Journal of Animal and Plant Sciences, 2020)
Sugarcane parental lines (Saccharum spp. hybrids) serve as a gene pool for sugarcane breeding and genetic improvement. Phenotypic evaluation is the most direct method to study genetic diversity among sugarcane parental lines. Morphological data of 31 phenotypic traits were collected from 130 major sugarcane parental lines for multivariate genetic analysis. The analysis revealed relatively high coefficients of variation and a wide range of frequencies. The extent of genetic diversity among the morphological traits reached a high level with the Shannon-Weiner index (Hs=0.858±0.026). The average genetic diversity index was greater for plant height and stem traits than all other traits. Relatively large genetic distances averaging 0.151 were observed among the 11 series of sugarcane parental lines, with the Guitang-series parental lines exhibiting the most genetic diversity (Hs=0.970±0.078). A dendrogram based on similarity coefficients clustered 130 major parental lines into three groups and six subgroups. The results provided key information on genetic diversity useful for the screening and selection of potential parents and the design of potential intercrosses.
Keywords: sugarcane parental line; phenotype; genetic diversity; diversity index; cluster analysis